PERANAN KEYAKINAN HAKIM DALAM PERKARA YANG PEMBUKTIANNYA LEMAH - Edwin Alexander Simaremare; Erdianto '; Ledy Diana (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2017)
The system of evidence in criminal procedure law which in its examination process demands the search for truth other than based on valid evidence and reaches the minimum limit of proof must also be supported again by the judge's belief in the truth has proved the defendant's defeat (beyond a reasonable doubt), the truth is realized really Based on undoubted evidence, so that the truth is considered to be of the essence of truth (materialele waarheid).Based on this understanding the authors formulate two formulation of the problem, namely: First, How the existence of the evidentiary system by using two evidences and judge's conviction ?. Second, What are the advocates and obstacles in generating judge confidence in weak systems of evidence?The type of research or approach used by the author is normative legal research. Normative legal research is a literary legal research. Because making the literature as the main focus of this research, the data source used, primary data, secondary data, and tertiary data, technical data collection in this study by literature study then by analyzing and processing the data qualitatively and generate descriptive data and then take the conclusion Deductively. From the research results of the problem there are three main points that can be concluded, namely: First, the existence of the evidentiary system by using two evidences and the judge's conviction has not been fully applied in the criminal justice system. Second, the supporters of the judge's judgment in determining the decision include the motivation or good faith of the judge to determine the fate of the defendant, the firmness of faith and devotion, the abilities and experience, the attitude, the circumstances, the background and the social status of the accused, other evidence is good because Conformity with valid or unlawful evidence, personal, family, environment in which the judge resides and the willingness of the judge to continue to study according to his discipline. While the obstacles for the judge in raising his conviction to determine the defendant's faults is the existence of bribery and intimidation or threats against the judge.Keywords: Role of Judge Belief-Weak System of Proof